Анализ распределения напряжений при радиально-ротационном профилировании ободьев колес - Пузырь, Р. Г.; Пузир, Р. Г.; Puzyr, Ruslan (КНТУ, 2015)
Вопросы определения поля напряжений при формоизменении ободьев колес из стальных заготовок на первом переходе радиально-ротационного профилирования являются актуальными. Интерес представляет определение напряжений на радиусе закругления профилирующего ролика, так как именно места сопряжений различных элементов профиля обода испытывают во время эксплуатации наибольшие нагрузки. Результаты теоретического исследования позволяют анализировать возникающие в процессе деформирования напряжения и определять совокупность технологических и конструкторских параметров процесса профилирования, которые оказывают значительное влияние на величину и распределение нормальных и касательных напряжений. Питання визначення поля напружень при формозміні ободів коліс із сталевих заготовок на першому переході радіально-ротаційного профілювання є актуальними. Інтерес представляє визначення напружень на радіусі закруглення профілюючого ролика, так як саме місця сполучень різних елементів профілю обода відчувають під час експлуатації найбільші навантаження. Результати теоретичного дослідження дозволяють аналізувати виникаючі в процесі деформування напруження і визначати сукупність технологічних і конструкторських параметрів процесу профілювання, які роблять значний вплив на величину і розподіл нормальних і дотичних напружень. The problems of determining the stress field at forming rim of steel billets at the first transition angular rotational profiling. Interest is the determination of the stresses on the radius of curvature of the profiling roller, as it places the coupling of different elements of the rim profile test during operation to maximum loads. The results of theoretical studies allow to analyze the deformation occurring during stress and to determine a set of technological and design parameters of the profiling process, which have a significant influence on the magnitude and distribution of normal and tangential stresses. Obtained according to different view of the blank deformation of the wheel rim as the design and not the sheet metal that can reveal an increasing amount of the profiling process, and keep a more accurate calculation of stresses and strains. It is shown that the radii of curvature of the wheel profile during the tensile deformation occur meridional stress that can lead to a dramatic thinning the blank that are not acceptable.
Аналіз розподілу напружень при радіально-ротаційному профілюванні ободів коліс
Analysis of stress distribution at the radial rotary profiling rim
Keywords: обод; профилирование; заготовка; радиус закругления; деформация; обід; профілювання; заготівля; радіус заокруглення; деформація; rim; profiling; blank; radius of curvature; distortion